Identifikasi Pola Aliran Sungai Bawah Tanah Daerah Karst di Desa Gebangharjo Kecamatan Pracimantoro Menggunakan Metode Tomography Resistivity Konfigurasi Wenner-Schlumberger - Yudi Purwanto; Darsono Darsono; Sorja Koesuma (Department of Physics, Sebelas Maret University, 2017)
This research is conducted using 4 lines data with 750 meters in length. Tomography resistivity with Wenner-Schlumberger configuration is used as this research methodology to take the data with a = 50 meters and n=1, 2, 3, 4, 5, 6. Resistivitymeter OYO 2119C McOHM-ELmodel is used as the instrument. Furthermore, the data is processed with two softwares; Res2Dinv ver. 3.56.22 to get 2D resistivity section and RockWork16to make 3D model of the site. The underground river’s chamber is made by hollow carbonate rocks with the resistivity of >412 Ωmand 117,6 Ωm – 412 Ωm for limestone’s resistivity as its capsrock. Researching to the depth of 173 meters, underground rivers are shown in the line 2 in the depth of 65 to 134 meters, 65 to 173 meters in the line 3, and in the cross section of line 3 and line 4. While in the first trajectory, another chamber is found within the depth of 12.5 to 40 meters. It is expected that the underground river is flowing to the south because of the chamber in third and fourth trajectory are lower than second trajectory.